High-altitude fall prevention method and device for power transmission line. Issue 1 (June 2021) - Wang, Zhigang; Ou, Yuexiong; Li, Hui; Zeng, Wenyuan; Gao, Quanzhe; Zou, Yu; Li, Peng
Abstract: This paper analyzes the structure of transmission line towers and live working conditions, and draws conclusions on the importance and necessity of studying the methods and devices of high-altitude fall prevention for transmission lines. Combining the actual situation of the pole and tower, in view of the poor manufacturing technology of the pole and tower anti-falling track, the size of the anti-dropping device and the track are not matched, and the connection point is misplaced, a new type of adjustable anti-dropping device is developed to address the cross-arm movement of personnel during live work. The alternate use of backup protection ropes and seat belts is cumbersome. An alternative safety rope was developed. Aiming at the transmission line towers without anti-falling tracks, a drone-based high-altitude fall prevention method was developed, and an anti-fall manipulator for high-altitude operations.